Perbandingan Keberhasilan Intubasi pada Upaya Pertama antara Video Laryngoscope dengan Direct Laryngoscope - Rahmaya Nova Handayani; Feldi Paputungan; Siti Haniyah (Journal of Telenursing (JOTING), 2023)
This study aims to determine differences in the success of intubation on the first attempt between video laryngoscopes and direct laryngoscopes. The method used is an experimental quasi-experimental type with a Two Group Post Test Design. The sampling technique was carried out by consecutive sampling with the research instrument, namely the observation sheet. Data were collected in the operating room of Prof. Dr. R. D. Kandou Manado with a sample size of 40 respondents, with 20 respondents intubating with a direct laryngoscope and 20 respondents intubating with a video laryngoscope using an unpaired t-test. The results showed that the probability value obtained was 0.035. In conclusion, the success rate of intubation on the first attempt with a video laryngoscope is higher than that of a direct laryngoscope. Keywords: Direct Laryngoscope, Intubation, Video Laryngoscope